Helical Tomotherapy Combined with Capecitabine in the Preoperative Treatment of Locally Advanced Rectal Cancer. (6th May 2014) - Huang, Ming-Yii; Chen, Chin-Fan; Huang, Chun-Ming; Tsai, Hsiang-Lin; Yeh, Yung-Sung; Ma, Cheng-Jen; Wu, Chan-Han; Lu, Chien-Yu; Chai, Chee-Yin; Huang, Chih-Jen; Wang, Jaw-Yuan
Abstract : The aim of this study was to evaluate the efficacy of helical tomotherapy plus capecitabine as a preoperative chemoradiotherapy (CRT) in patients with locally advanced rectal cancer (LARC). Thirty-six LARC patients receiving preoperative CRT were analyzed. Radiotherapy (RT) consisted of 45 Gy to the regional lymph nodes and simultaneous-integrated boost (SIB) 50.4 Gy to the tumor, 5 days/week for 5 weeks. Chemotherapy consisted of capecitabine 850 mg/m 2, twice daily, during the RT days. Patients underwent surgery 6–8 weeks after completion of CRT. Information was collected for patient characteristics, treatment response, and acute and late toxicities. Grade 3/4 (G3+) toxicities occurred in 11.1% of patients (4/36). Sphincter preservation rate was 85.2% (23/27). Five patients (14.3%) achieved pathological complete response. Tumor, nodal, and ypT0-2N0 downstaging were noted in 60% (21/35), 69.6% (16/23), and 57.1% (20/35). Tumor regression grade 2~4 was achieved in 28 patients (80%). After a median follow-up time of 35 months, the most common G3+ late morbidity was ileus and fistula (5.7%, 2/35). The study showed that capecitabine plus helical tomotherapy with an SIB is feasible in treatment of LARC. The treatment modality can achieve a very encouraging sphincter preservation rate and a favorable ypT0-2N0 downstaging rate without excessive toxicity.